FC040: Kidney Transplantation in Childhood-Onset ANCA-Associated Vasculitis: Outcomes in a Multicentre Cohort. (3rd May 2022) - Allinovi, Marco; Trivioli, Giorgio; DI Marcantonio, Elio; Jawa, Natasha; Trivelli, Antonella; Subun, Chantida; Majib, Biplap; Rubik, Jacek; Mohammad, Aladdin; Testa, Sara; Jahnukainen, Timo; Gulhan, Bora; et al.
Abstract: BACKGROUND AND AIMS: ANCA-associated vasculitis (AAV) is rare among children but leads to kidney failure (KF) in almost 30% of cases with renal involvement [1]. Kidney transplantation (KT) is the treatment of choice in adults with AAV and KF, while data among children are limited to small case series [2, 3]. We report the outcomes of KT in a multicentre cohort of patients with childhood-onset AAV. METHOD: Patients with AAV diagnosed before the age of 18 years who had undergone KT were identified at one Canadian and 20 European centres. We analysed patient and graft survival and the rates of rejection, AAV relapse and infections. Eighteen patients from this cohort had already been reported in previous articles [1, 2]; their follow-up was extended and further relevant data were retrieved. RESULTS: We included 55 patients, of whom 38 (69%) had microscopic polyangiitis (MPA) and 17 (31%) granulomatosis with polyangiitis (GPA). Their median age at diagnosis and transplantation was, respectively, 12 (interquartile range, IQR 9–14) and 14 (IQR 12–16) years (Table 1). Living donor transplantation was performed in 20 cases (36%) and deceased donor transplantation in 35 (64%). At the time of transplantation, all patients were in clinical remission and ANCA was positive in 14/54 (26%). As immunosuppressive therapy, 46 patients (84%) received glucocorticoids, tacrolimus and either mycophenolate mofetil or azathioprine. The median follow-up after transplantation was 54 months (IQR 21–91). Acute rejection was reported in 22 patients (40%), 12 of whom experienced it during the first post-transplant year, while chronic rejection was established in two (4%). AAV relapsed in five cases (9%) and involved the graft in 4/5. Positive ANCA at transplantation was significantly associated with relapse (29% versus 2%; P = 0.02). Infections occurred in 34 patients (62%), and were mainly bacterial infections of the urinary tract or viral infections due to CMV (8/34), EBV (5/34) and BK virus (4/34). No patient developed malignancy. At last visit, all patients were alive and 48 (87%) had a functioning graft. Graft function impairment (eGFR <60 mL/min/1.73 m 2 ) developed in 21 patients and seven (13%) of these lost their graft due to acute (6/7) and chronic rejection (1/7). Outcomes and complication rates did not differ significantly between the MPA and the GPA group (Table 1 ). Graft function impairment was associated with rejection and positive ANCA at transplantation, but not with age at diagnosis and at transplantation, ANCA specificity, the type of donor or the immunosuppressive regimen (Figure. 1 ). CONCLUSION: KT in childhood-onset AAV has a relatively good graft and patient survival, while the rate of complications and the risk of vasculitis relapse appear low. Positive ANCA at the time of transplantation may be a risk factor for both AAV relapse and graft function impairment.